(untitled) (Mustansiria Dental Journal, 2024)
Forty resin simulated root canals with standardized curvature prepared for this study, divided into four groups ten canals for each group. Thirty canals were prepared with rotary endodontic instruments, profile 04, profile 04, 06 and protaper, ten canals for each type, with slow speed contra angle hand piece (300 rpm) using crown — down technique the other l0 canals were prepared with stainless steel k-flexo hand instrument using step — back technique. The total time required for preparation was calculated. The resin blocks were scanned; the pre-instrumented and post - instrumented images were stored in the computer and superimposed for two dimensional evaluation of canals preparation using Adobe photoshope 8.0 and Corel draw 9. For the coronal portion the amount of canal substance removed was calculated at 7mm, 9mm, llmm levels from the working length. For the apical curvature the centering ratio was calculated at 2mm and 4mm level from the working length. The results showed that the amount of canal substance removed from the coronal portion by protaper was statistically higher than other groups with statistically less ability to stay center in the canal than profile rotary instruments but more ability to preserve apical curvature than k-flexo hand instruments with less time required for preparation. K-flexo files showed statistically less amount of canal substance removal at coronal portion and statistically higher centering ratio than other groups, and require more time for canals preparation .